The Role of Risk Assessment in Health Care Institutions - Branislav Marić (Journal of Womens Healthcare & Midwifery Research, 2026)
Health care institutions represent one of the most challenging working environments because they combine complex clinical activities with continuous exposure to numerous occupational hazards. Health care professionals work under conditions that require rapid decision-making, high responsibility, physical endurance, and emotional resilience. At the same time, they are exposed to biological agents, hazardous chemicals, ionizing radiation, manual handling of patients, workplace violence, psychological stress, and irregular working hours.